Analysis of laterally loaded pile in layered soils [electronic resource] - Cheong, Chee Hoe, 1987-, author (2011)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2011